Procedures for Reporting Financial Statements of Public Companies to The Indonesian Stock Exchange (Study In PT. Gaya Abadi Sempurna, Tbk) - Muhammad Nawawi; Prasadhita, Chandra; Noer Fahrezi, Ahmad (Management Science Research Journal, 2024)
This study aims to explain and analyze the procedure for reporting the financial statements of PT Gaya Abadi Sempurna, Tbk to the Indonesia Stock Exchange based on Bapepam RI Regulation Number X.K.2: Submission of Periodic Financial Statements of Issuers or Public Companies, SEOJK RI Number 4 /SEOJK.04/2022, and IDX Regulation Number I-E concerning Obligations to Submit Information. The research method used is descriptive research. The data source in this study uses secondary data as the main data. Data collection methods using literature study and field research. The method used in analyzing and processing the collected data is qualitative analysis. Based on the results of the research, the company reports its financial statements to the Indonesia Stock Exchange by Bapepam RI Regulation Number X.K.2: Submission of Periodic Financial Statements of Issuers or Public Companies, SEOJK RI Number 4 /SEOJK.04/2022, and IDX Regulation Number I-E concerning Obligations to Submit Information. Several internal and external obstacles were found. Internal errors such as format, nominal, or account errors in the process of preparing financial statements, and external errors such as system errors/maintenance on the Indonesia Stock Exchange web itself. Keywords: procedures, reporting, financial statements, public company